Economic Impacts of Sports Tourism on the Host Population - (A Case Study of Commonwealth Games-2010) - Taxak , R H; Kumar, Mohan (Gyan Management Journal, 2011)
Tourism acts as a unifying force, witness dynamism and helps to learn about a country and the travelling nationals of other countries. This experience helps in fostering goodwill and understanding between various linguistic, religious and communal groups living in different parts of the world. Development of the tourism industry provides employment to many and has helped in building a strong economic structure which in turn has helped in attracting international tourists and the foreign exchange. Tourism also contributes to the development of the local handicrafts and cottage industries. These days, new trends are emerging in the tourism industry in which sports tourism is one of them. Sports tourism not only represents the image of the destination but also enhance the employment opportunities for the local community. The study is mainly based to know economic impacts of sports tourism on the host population in Delhi region.
Keywords: Sports Tourism; Economic Impacts; Likert Scale; SPSS; Chi-square test